Auditoría Operativa y su incidencia en la toma de Decisiones de "Comisariato Kerly" en la parroquia el Carmen, Cantón La Maná, periodo 2020 - Medina Briones, Nuris Jessenia (2022)
The importance of the audit lies in the function of subsequent control that it exerts on managerial actions, through its results it is possible to know the existing irregularities that threatened the efficiency, economy and effectiveness of the company, being an advantage to have a comprehensive vision. because it allows constructive suggestions and recommendations to improve the overall productivity of the company. That is why this project had the general objective of executing an operational audit to determine the degree of efficiency, effectiveness and economy of the operations of the company Comisariato Kerly, in the El Carmen parish, La Maná canton, province of Cotopaxi, Year 2020, allowing for proper decision making. The types of research used were bibliographic, field and inductive, deductive, analytical methods and survey and interview techniques. Through the diagnosis of the current situation, it was possible to know that there was no prior history of the development of operational audits, an aspect that made it difficult to make decisions regarding preventive or corrective activities effectively. Among the relevant findings, the non-existence of a formal documentation of the organizational objectives was mentioned, the manual of functions has not been disseminated among its collaborators, in addition, it was possible to know that the level of risk and confidence of the internal control was moderate and a moderate level of efficiency and effectiveness. Regarding the calculation of the level of incidence, hypothesis Ha was accepted, which mentions that the operational audit is not independent of the decision-making of the Kerly Commissariat of the La Maná canton. Finally, as a proposal, a decision-making manual was designed that was structured by the generalities of the commissary, the description of the purchasing processes, suppliers, sales, physical inventory taking and merchandise entry through flow charts.